POTENTIAL AND UTILIZATION OF CORN HARVEST WASTE BASED ON ANIMAL FEED PROCESSING IN TAROANG DISTRICT, JENEPONTO DISTRICT - Hasanuddin; Mustamin, Siti Walidah; Amin, Saifuddin; Reski Adi (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2025)
This service aims to identify the potential and utilization of corn harvest waste as raw material for animal feed in Taroang District, Jeneponto Regency. Corn harvest waste, such as stems, leaves and cobs, is often not utilized optimally and becomes an environmental problem. Through community service carried out by a team from Muhammadiyah University of Makassar, a series of activities were carried out to introduce corn waste processing technology using a chopper. Demonstrations and training on the use of chopping equipment were carried out to increase the community's understanding and skills in processing corn waste into quality animal feed. The results of this activity show that the use of corn waste as animal feed has great potential to increase the economic value of agricultural waste and reduce environmental impacts. Apart from that, the people involved in this program, especially the